Forms Of Legal Protection In Timor Leste For Foreign Citizens Who Have Been Sentenced To Death in Their Country of Origin - Constantino Magno; Richard Alfred Xavier Da Conceicao; Elvira Dos Santos Afonso; Rogerio Menezes Da Costa; Reinaldo Fransisco Luis (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The purpose of this research is to find out "What is the form of protection of Timorese law for foreign nationals who receive death in their country? This research was conducted at the Criminal Investigation Department at the Caicoli PNTL Headquarters with the target of parties or elements whose functions as Investigators, namely members, field chief executives and their Commanders at the Criminal Investigation Department at the Caicoli PNTL General Headquarters. How to obtain data by co-authorization, conduct interviews (Interviews), and then analyze deductively or inducively and then presented descriptively, namely explaining, descripting, and describing according to problems that are closely related to this research. The protection of the law of Timor Leste against foreign nationals who receive the death penalty in their country, This is reflected in the Constitution of the Republic of Timor Article 1 paragraph (1) "The Democratic Republic of Timor Leste is a democratic, sovereign, independent and united state, based on the force of law, the will of the people and the honor of human dignity". Consequently, Timor-Leste is a country of law that the supreme power in the country is the law Thus Timor-Leste is committed to human rights and legal protection, including for foreign nationals facing the death penalty in their home country. The forms of legal protection that can be provided by Timor-Leste are Asylum, International Protection, Diplomacy, Negotiation, Legal Aid, Constitutional Protection and Public Awareness Campaigns. Timor-Leste seeks to provide effective legal protection for foreign nationals facing the threat of the death penalty in their home countries.